The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cge.13238
|View full text |Cite
|
Sign up to set email alerts
|

INTU‐related oral‐facial‐digital syndrome type VI: A confirmatory report

Abstract: Oral-facial-digital (OFD) syndromes are a subgroup of ciliopathies distinguished by the co-occurrence of hamartomas and/or multiple frenula of the oral region and digital anomalies. Several clinical forms of OFD syndromes are distinguished by their associated anomalies and/or inheritance patterns, and at least 20 genetic types of OFD syndromes have been delineated. We describe here a child with preaxial and postaxial polydactyly, lingual hamartoma, a congenital heart defect, delayed development and cerebellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, we can speculate that the detected INTU variant adds to the burden of the IFT140 variants on proper functioning of the IFT-A complex. Recent literature has shown that mutations in INTU are causative for a short-rib polydactyly syndrome phenotype ( Toriyama et al, 2016 ; Bruel et al, 2018 ). The INTU variant c.1354G > A that was detected in patient 2 has previously been described to be causative in a 13-year old female with nephronophthisis, ESRD at 10 years of age and growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can speculate that the detected INTU variant adds to the burden of the IFT140 variants on proper functioning of the IFT-A complex. Recent literature has shown that mutations in INTU are causative for a short-rib polydactyly syndrome phenotype ( Toriyama et al, 2016 ; Bruel et al, 2018 ). The INTU variant c.1354G > A that was detected in patient 2 has previously been described to be causative in a 13-year old female with nephronophthisis, ESRD at 10 years of age and growth retardation.…”
Section: Discussionmentioning
confidence: 99%
“… Note : The following genes are not listed due to lack of sufficient evidence that they are associated with JS (only one family, insufficient clinical information, and/or lack of biallelic variants): TTC21B (no biallelic variants in JS, variants reported in families with other ciliopathies; Davis et al, ), ZNF423 (one family with possible JS; Chaki et al, ), CLUAP1 (one family with JS; Johnston et al, ), EXOC8 (one family with JS; Dixon‐Salazar et al, ), CELSR2 (one family in each of two papers, variants not reported for one family; Shaheen et al, ; Vilboux et al, ), POC1B (one family; Beck et al, ), CEP164 (one family with JS, variants reported in families with other ciliopathies; Chaki et al, ; Vilboux and others, ), INTU (insufficient imaging informaton in several patients with ciliopathy phenotypes; Bruel et al, , ; Toriyama et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Seizures have been described in a number of individuals with JS (minimum prevalence 10%; Bachmann-Gagescu, and must be specifically sought out during recording of the medical history. No single seizure type appears to dominate and there Bruel et al, 2017Bruel et al, , 2018Toriyama et al, 2016). Abbreviations: ACC, agenesis of the corpus callosum; Chr, chromosome; OFD, oral facial digital features; PCD, primary ciliary dyskinesia; PD, polydactyly; Unk, unknown (not found in the UW cohort).…”
Section: Molecular Diagnosis Of Jsmentioning
confidence: 99%
“…But he did not have any developmental delay. Molecular analysis revealed a single nucleotide variant in INTU gene and a deletion encompassing it [NM_015693.3; p.(Gly523Ser) and deletion in 4q28.1] (Bruel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%